2018
DOI: 10.1016/j.drugpo.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Peer-to-peer injection: Demographic, drug use, and injection-related risk factors

Abstract: Background: Peer-to-peer injection (either providing or receiving an injection to/from a person who injects drugs [PWID]) is common (19%-50%) among PWID. Most studies of peer-to-peer injection have focused on receiving injection assistance, with fewer examining providing injection assistance and none considering characteristics of PWID who do both. We examined characteristics of PWID by peer-to-peer injection categories (receiving, providing, both, and neither) and determined if these behaviors were associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 62 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…In addition, we found that providing injection assistance was also associated with both low and high frequency initiation; only one study has reported this association previously (Bluthenthal et al, 2014). Peer-to-peer injection assistance is common in populations of PWID (Kral et al, 1999;Lamb et al, 2018) and is likely related to injection initiation due to the skill that PWID who provide injections to others possess (Simpson et al, 2018). A focus on working directly with PWID who provide injection assistance is warranted.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…In addition, we found that providing injection assistance was also associated with both low and high frequency initiation; only one study has reported this association previously (Bluthenthal et al, 2014). Peer-to-peer injection assistance is common in populations of PWID (Kral et al, 1999;Lamb et al, 2018) and is likely related to injection initiation due to the skill that PWID who provide injections to others possess (Simpson et al, 2018). A focus on working directly with PWID who provide injection assistance is warranted.…”
Section: Discussionmentioning
confidence: 79%
“…We were also interested in drug use factors that might be associated with injection initiation frequency. We collected information on peer-to-peer injection assistance which includes injecting another PWID (but not for their first inject) and receiving an injection from another PWID (Kral et al, 1999;Lamb et al, 2018). In addition, we collected information on frequency of injecting with other PWID and injecting in public spaces.…”
Section: Study Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Formalized PAIPs are intended to bene t SCS clients through safe injection education and expert assistance, while protecting recipients from exploitive or unsafe relationships with would-be injection providers (16) and the risks associated with sharing equipment and drugs. Public health leaders and researchers have recommended peer assist be a standard part of supervised consumption services in Canada for years (5,6). Research continues to emerge to inform the implementation of PAIP on a large scale.…”
Section: The Public Health Value Of Peer-assistmentioning
confidence: 99%
“…This prohibition effectively barred PWID who wished to access the SCS but were unable to self-inject. These individuals were left to inject in hurried, unsafe, and unclean conditions, leading public health leaders and researchers to call on government to allow peer assist within supervised consumption settings (5,6).…”
Section: Introductionmentioning
confidence: 99%